UPACARA BIYUKUKUNG (KEARIFAN LOKAL MASYARAKAT BALI DALAM MENJAGA TEO-AGRIKULTUR) - Ni Nyoman Suastini (UHN IGB Sugriwa Denpasar, 2021)
Biyukukung ceremony was carried out by Balinese people whoworked in agriculture, especially rice farming. This ceremony was relatedwith Balinese people’s effort religiously to gained prosperity for their ricein the field. As a rice farmer, Balinese people often had adversity in theirfield, liked damaged by pests, lacked of water, and more. As a religiouspeople, they used this ceremony to avoid any adversity. Biyukukungceremony was carried out by farmers, started from prepared the facilitieslike banten and other which related with the ceremony. The meaning ofthis ceremony was an expression of farmers’ thankful to God in the form ofhis manifestation as Dewi Sri and Dewa Wisnu which provided safety andgrowth the rice fertilely, protected from the pests, and other damaged.That was why Balinese people carried out the ceremony which hadinherited by every generation. This ceremony also made different meaningof agriculture group, which was not only about farming. Moreover, themean was combined the concept of Hindu’s theology and farming. Thistradition then became a unified in farming system, so that the religionceremony and farming activity be related to each other. Balinese peoplealways depended to God for their safety, so that all of their action, includedfarming, was related. This relation made Bali unique, there was no linebetween religion and culture in their daily life. Thus, “BiyukukungCeremony” had function and meaning to prayed the rice growth fertilelyand also the field safety, so that the farmers could harvest well accordingto their expectation.